Analisa Kinerja Biaya Konsep Green Pada Bangunan Utama Flour Mill Plant Berbasis Value Engineering dan Life Cycle Cost Analysis - Kurniawan, Iwan; Husin, Albert Eddy (Jurnal Aplikasi Teknik Sipil, 2025)
<div class="[–thread-content-max-width:32rem] @[34rem]:[–thread-content-max-width:40rem] @[64rem]:[–thread-content-max-width:48rem] mx-auto flex max-w-(–thread-content-max-width) flex-1 text-base gap-4 md:gap-5 lg:gap-6 group/turn-messages focus-visible:outline-hidden" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="bd35d8a3-66a1-4a83-a1f5-0c83ca2816fb" data-message-model-slug="gpt-4o"> <div class="[–thread-content-max-width:32rem] @[34rem]:[–thread-content-max-width:40rem] @[64rem]:[–thread-content-max-width:48rem] mx-auto flex max-w-(–thread-content-max-width) flex-1 text-base gap-4 md:gap-5 lg:gap-6 group/turn-messages focus-visible:outline-hidden" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="bd35d8a3-66a1-4a83-a1f5-0c83ca2816fb" data-message-model-slug="gpt-4o"> In accordance with the mission of the Sustainable Development Goals 2030, that by 2030 the new building will have a green concept of 100% and an existing building of 60%. With the Value Engineering and Life Cycle Cost Analysis methods, the application of the green concept to the Main Building of the Flour Mill Plant is used for analysis using Structural Equation Modelling – Part Least Square (SEM-PLS). The result of this study is that there are 10 factors that affect the cost performance of the Green project on the Main Building of the Flour Mill Plant, namely Project Manager Performance, Energy Efficiency, Technical Specifications, Provision of Parking Lots, Management Commitments, Water Sources, Analysis Functions, Waste Handling Systems, Selection of Alternative Materials and Energy Costs. The Value Engineering method resulted in cost savings of 14.21% of Green costs, LCCA showed a payback period with time = 3.11 years or approximately 3 years and 11 months for the application of the Green concept to the main flour mill plant building.